Aroma and quality of carrot dried using a microwave-convective drying system as affect by temperature gradient. Issue 1 (1st January 2020) - Xu, Wanxiu; Yuan, Jianfeng; Tian, Jinghong; Li, Gang; Sun, Xiaoming; E, Shiju; Zhu, Guanyu; Xia, Ziming; Wang, Dongyun; Wang, Tao; Wu, Jiangmiao; Xiao, Zhen
ABSTRACT: A real-time aroma monitoring system to control a microwave combined with hot air drying (MHAD) process of carrot was designed. The samples were first dried at four fixed temperature gradients of 2°C/mm, 4°C/mm, 6°C/mm and 8°C/mm to investigate the effect of temperature gradient on the aroma diffusion. Carrot samples could be dried in a shorter time from 140 min to 100 min from low-temperature gradients 2°C/mm to high-temperature gradient 8°C/mm. Main volatiles lost more and charring volatiles was induced at highest temperature gradients 8°C/mm. A fuzzy logic controller was then designed and employed to control the drying process. Based on the temperature curve achieved under fuzzy logic control, a simple linear control method was developed where e-nose online assistance could be omitted. Color, vitamin C, rehydration ratio and sensory evaluation were performed after rehydration. With the new control strategies, carrot color and overall appearance were intact and less time and energy were consumed.